Maternal FADS2 single nucleotide polymorphism modified the impact of prenatal docosahexaenoic acid (DHA) supplementation on child neurodevelopment at 5 years: Follow-up of a randomized clinical trial. Issue 10 (October 2021) - Gonzalez Casanova, Ines; Schoen, Meriah; Tandon, Sonia; Stein, Aryeh D.; Barraza Villarreal, Albino; DiGirolamo, Ann M.; Demmelmair, Hans; Ramirez Silva, Ivonne; Feregrino, Raquel Garcia; Rzehak, Peter; Stevenson, India; Standl, Marie; et al.
Summary: Background: Variability in the FADS 2 gene, which codifies the Delta-6 Desaturases and modulates the conversion of essential n-3 and n-6 fatty acids into long-chain polyunsaturated fatty acids, might modify the impact of prenatal supplementation with n-3 docosahexaenoic acid (DHA) on neurodevelopment. Objective: To assess if maternal FADS2 single nucleotide polymorphisms (SNPs) modified the effect of prenatal DHA on offspring development at 5 years. Design: We conducted a post-hoc interaction analysis of the POSGRAD randomized controlled trial (NCT00646360) of prenatal supplementation with algal-DHA where 1094 pregnant women originally randomized to 400 mg/day of preformed algal DHA or a placebo from gestation week 18–22 through delivery. In this analysis, we included offspring with information on maternal genotype and neurodevelopment at 5 years (DHA = 316; Control = 306) and used generalized linear models to assess interactions between FADS2 SNPs rs174602 or rs174575 and prenatal DHA on neurodevelopment at 5 years measured with McCarthy Scales of Children's Abilities (MSCA). Results: Maternal and offspring characteristics were similar between groups. At baseline, mean (±standard deviation) maternal age was 26 ± 5 years and schooling was 12 ± 4 years. Forty-six percent (46%) of the children were female. Maternal minor allele frequencies were 0.37 and 0.33 for SNPs rs174602 and rs174575, respectively. There were significant variations by SNP rs174602 and intervention group (p for interactions <0.05) where children in the intervention group had higher MSCA scores on the quantitative (DHA: mean ± SEM = 22.6 ± 0.9 vs. Control = 19.1 ± 0.9, mean difference (Δ) = 3.45; p = 0.01) and memory (DHA = 27.9 ± 1.1 vs. Control = 23.7 ± 1.1, Δ = 4.26; p = 0.02) scales only among offspring of TT (minor allele homozygotes). Conclusions: Maternal FADS2 SNP rs174602 modified the effect of prenatal DHA on cognitive development at 5 years. Variations in the genetic make-up of target populations could be an important factor to consider for prenatal DHA supplementation interventions.